Astrocytic MicroRNAs and Transcription Factors in Alzheimer’s Disease and Therapeutic Interventions - Ajmal Nassar; Triveni Kodi; Sairaj Satarker; Prasada Chowdari Gurram; Dinesh Upadhya; Fayaz SM; Jayesh Mudgal; Madhavan Nampoothiri (Cells, 2022)
Astrocytes are important for maintaining cholesterol metabolism, glutamate uptake, and neurotransmission. Indeed, inflammatory processes and neurodegeneration contribute to the altered morphology, gene expression, and function of astrocytes. Astrocytes, in collaboration with numerous microRNAs, regulate brain cholesterol levels as well as glutamatergic and inflammatory signaling, all of which contribute to general brain homeostasis. Neural electrical activity, synaptic plasticity processes, learning, and memory are dependent on the astrocyte–neuron crosstalk. Here, we review the involvement of astrocytic microRNAs that potentially regulate cholesterol metabolism, glutamate uptake, and inflammation in Alzheimer’s disease (AD). The interaction between astrocytic microRNAs and long non-coding RNA and transcription factors specific to astrocytes also contributes to the pathogenesis of AD. Thus, astrocytic microRNAs arise as a promising target, as AD conditions are a worldwide public health problem. This review examines novel therapeutic strategies to target astrocyte dysfunction in AD, such as lipid nanodiscs, engineered G protein-coupled receptors, extracellular vesicles, and nanoparticles.